Preparation of Silver Nanoparticles and Their Industrial and Biomedical Applications: A Comprehensive Review - Adnan Haider; Inn-Kyu Kang (Advances in Materials Science and Engineering)
Silver nanoparticles (Ag-NPs) have diverted the attention of the scientific community and industrialist itself due to their wide range of applications in industry for the preparation of consumer products and highly accepted application in biomedical fields (especially their efficacy against microbes, anti-inflammatory effects, and wound healing ability). The governing factor for their potent efficacy against microbes is considered to be the various mechanisms enabling it to prevent microbial proliferation and their infections. Furthermore a number of new techniques have been developed to synthesize Ag-NPs with controlled size and geometry. In this review, various synthetic routes adapted for the preparation of the Ag-NPs, the mechanisms involved in its antimicrobial activity, its importance/application in commercial as well as biomedical fields, and possible application in future have been discussed in detail.